ANALYSIS OF PHARMACEUTICAL COMPANIES’ ACTIVITIES THAT ARE DIRECTED TO PHYSICIANS IN EGYPT - M. M. Bahlol; T. P. Lagutkina (Бюллетень сибирской медицины)
Purpose. Pharmaceutical market is one of the largest world markets with its own conditions. In Middle East, Egypt is a major pharmaceutical emerging market and has geographical, historical and political effective leading role among Arab countries. This research aims to investigate pharmaceutical companies’ activities in Egypt directed to physicians.Methodology. Urveying through simple random probability sampling is the approach appropriate for broad and representative overview of situation in research. Therefore, a survey of 1068 physicians was conducted through interviews and establishing structured data collection questionnaire.Originality. This is the first empirical paper to investigate pharmaceutical companies’ activities directed to physicians in pharmaceutical market of Egypt. These activities include identifying pharmaceutical companies through visits of medical representatives, analysis of those visits, frequency of medical representatives’ visits, characteristics of information introduced by medical representatives to physicians, physicians’ trust in provided information, spending of pharmaceutical companies on physicians, promotional techniques applied by medical representatives. These findings are useful for managers in pharmaceutical industry. They can be also useful in other industries such as medical equipment.Findings. Pharmaceutical companies are employing medical representatives widely, as the most effective and widely-applied promotion tool in Egypt.Practical Implications. Coordinate marketing management vision with pharmaceutical market real context will lead to synergism effect in utilizing medical representatives’ activities.